Residual Coolant Quantity in High Pressure Vessel Of PWR–440 (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The dynamic behavior of the remaining thermal carrier at different interval times in the high-pressure cylinder of a VVER – 440 MW reactor has been studied, when the sudden leakage occurred in the first cooling loop. The study included the effect of the diameter and the location of the leakage hole, in addition to the temperature of the thermal coolant within the first cooling loop prior to the start of the leakage process.         An experimental equation was developed for the distance of the remaining thermal carrier within the high-pressure cylinder as a function of time-based on the relative diameter, the relative height of the coolant flow and the relative temperature of the thermal coolant. Important conclusions are made that could contribute to building nuclear safety systems for reactors of the type (Pressurized Water Reactor), PWR– 440 with the power of 440 Mw.